PENDIDIKAN PERAN ORANG TUA MENGERJAKAN PEKERJAAN RUMAH - ‘Aisyah, Nur; Herianingtyas, Nur Luthfi Rizqa (LPPM Universitas Bina Bangsa, 2023)
The involvement of parents plays a crucial role in their children's education at home. Additionally, parents' presence is vital in educating children who are unaware of the silent spread of the Corona virus within their household. It is imperative to prevent the pandemic from infecting or spreading among the family members. According to parental opinions, homeschooling has proven to be a successful approach, although it does not imply that traditional schooling is less effective, especially for children aged 8 and above. To conduct this study, a phenomenological qualitative approach was employed, utilizing a questionnaire survey to collect data. The primary focus of this research was on parents with children aged 5 to 8 years, specifically those with children who were 5 years old. The findings of this study reveal that parents can enhance their bond with their children while actively witnessing the development of their children's learning abilities